Gold and silver recuperation of sulphured minerals in a quarz matrix - Azañero Ortiz, Ángel (2007)
The mineral That is matter of the present work of investigation comes from the department of the Libertad, province of Otuzco, the mining company Koricolqui S.A. The study by the x- rays diffraction confi rms that the greater component of the sample is guartz in 91,74 %. In the characteristic of the sample by the method by polarizing microscope of refl ected light, the following minerals are observed: electrum, arsenopirita, marcasite, calcosita, galena, esfalerita, rutilo, goethite, tetraedita and gangues; which are like very small particles that they make diffi cult his treatment. The tests of fl otation of the initial sample are not satisfactory because the recoveries are as much for low gold and silver that is of 59,11% and 52,51% respectively. For that reason previously I am made a preconcentration with the centrifugal “Falcon” and relave of the “Falcon” just enters the fl otation process. The results in these conditions improve substantially arriving at recoveries from gold and silver from 85,67% and 75,72% respectively with a granulometría from 66% -200 mesh. Parallelly cyaniding tests were run with the initial sample stops: 12,18,24,30 and 36 hours, with the same granulometría that work in the fl otation. The results indicate that even 36 hours of leaching a gold recovery is obtained of 81,21%, however for the silver is low in 49,81%.